71 LYSOPHOSPHATIDIC ACID INDUCES CYCLOOXYGENASE 2 EXPRESSION AND PROSTAGLANDIN E2 PRODUCTION IN HUMAN PRIMARY BRONCHIAL EPITHELIAL CELLS. (1st March 2007) - Zhao, Y.; He, D.; Stern, R.; Kalari, S.; Spannhake, E. W.; Natarajan, V.
Abstract : Rationale: We have demonstrated that transactivation of EGF-R by lysophosphatidic acid (LPA) partly regulates IL-8 secretion in human bronchial epithelial cells (HBEpCs). The present study provides evidence that crosstalk between G protein-coupled LPA receptors and EGF-R regulates LPA-induced cyclooxygenase 2 (COX-2) expression and prostaglandin E2 (PGE2 ) production in HBEpCs. Methods/Results: LPA (1 μM) treatment induced COX-2 expression at mRNA and protein levels but had no effect on COX-1 expression. Down-regulation of COX-2 by transfection of COX-2 siRNA blocked LPA-induced PGE2 release in HBEpCs. Pretreatment of HBEpCs with pertussis toxin (PTx), intracellular calcium chelator (BAPTA-AM), overexpression of dominant negative PKC delta, IKK inhibitor (Bay11-7082), JNK inhibitor (JNKi), transfection of c-Jun siRNA, or C/EBPβ siRNA blocked LPA-induced COX-2 expression. Further, down-regulation of EGF-R by EGF-R siRNA or pretreatment with EGF-R tyrosine kinase inhibitor (AG1478) partly attenuated LPA-induced phosphorylation of C/EBPβ, COX-2 expression, and PGE2 release but not phosphorylation of IκB, JNK1/2, and nuclear localization of NF-κB. Conclusions: We show here that LPA induces COX-2 expression through intracellular calcium, activation of PKC delta, NF-κB, JNK/AP-1, C/EBPβ, and EGF-R transactivation. Since COX-2 is anti-inflammatory in the airway, the present results suggest that LPA plays a protective role in airway inflammation and remodeling. Supported by NIH grant HL 71152 to V.N.